2016
DOI: 10.18488/journal.73/2016.4.1/73.1.22.35
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths and Life Satisfaction of Teachers in Ghana

Abstract: Contribution/ OriginalityThis study is one of very few studies which have investigated Peterson and Seligman (2004) character strengths in Ghana and it identified unique distribution of the strengths among teachers. The top 7 strengths indicate teachers scoring high on wisdom and knowledge strengths which is unique from studies using general samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
2
9
0
1
Order By: Relevance
“…It is very important for the management of TVET HLIs to keep up a good service quality and corporate image since it will affect the level of students' satisfaction. Students as customers are the major concern for an educational institution, and the satisfaction of them shows the success or failure of the institution's operation (Abasimi & Xiaosong, 2016;Austin & Pervaiz, 2017). Service quality and corporate image are important constructs in determining satisfaction (Bapat, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is very important for the management of TVET HLIs to keep up a good service quality and corporate image since it will affect the level of students' satisfaction. Students as customers are the major concern for an educational institution, and the satisfaction of them shows the success or failure of the institution's operation (Abasimi & Xiaosong, 2016;Austin & Pervaiz, 2017). Service quality and corporate image are important constructs in determining satisfaction (Bapat, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted showed ties between an individual's satisfaction with life and personality traits [48]; academic performance [49]; emotional intelligence [50] and intrinsic motivation [51]. Furthermore, a number of studies found connections between a teachers' satisfaction with life and job satisfaction [52]; organizational isolation level [53]; burnout Level [54], creativity, profundity, willingness for teamwork, level of forethought and appreciation [55]; and social support [56]. In light of these studies it can be assumed that a teachers' satisfaction with life is interlinked with a number of variables related to their professional life.…”
Section: Introductionmentioning
confidence: 99%
“…This may mean that the features of Turkish society such as prudent child-rearing and prudent economic activities are reinforced by curriculums. Considering the other variables related to prudence, it is thought that this situation may contribute to the life satisfaction of students (Abasimi, Gai, & Wang, 2017). While self-regulation, another character strength related to the virtue of temperance, were identified as one of the least possessed character strengths among people living in 75 different countries (McGrath, 2015), it drew attention as the second most common character strength in LSCC.…”
Section: Resultsmentioning
confidence: 99%